Technological Knowledge of Gynecological Pedagogy in Teaching Jawi Subjects Islamic Education Teachers - Zaleha Muhammad; Mohd Aderi Che Noh (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This study aims to identify the stage of Content Pedagogy Technology Knowledge and GPI teaching practices for Jawi subjects. Respondents in this study consisted of 378 Islamic Education teachers teaching in low schools throughout Malaysia. Quantitative study methods were used, and random sampling was carried out for data collection. Cronbach's Alpha analysis of the instrument used shows a high trustworthiness value for the constructs tested. This study was analyzed descriptively and inference using the SPSS version 26 application. Based on the survey results, respondents indicated a high level for five of the seven aspects of PTPK, namely technology, pedagogy, content, content pedagogy, and content technology. At the same time, their perceptions were more superficial in terms of technology. Content pedagogy and technology. From the aspect of GPI teaching practice, the three components, namely the beginning, development, and closing, are at a high stage, compared to the BBM component, which shows a simple step. In addition, there is a significant and positive relationship between each PTPK component and the GPI teaching practice component. The PLS SEM analysis shows that the model proposed in the study shows a good fit for all the measured variables. Implications and recommendations are put forward for providing valuable input to the Malaysian Ministry of Education (KPM), schools, teachers and the community to improve the quality of teacher teaching practices. Islamic education.